2022
DOI: 10.1007/s00415-022-11071-5
|View full text |Cite
|
Sign up to set email alerts
|

The CCAS-scale in hereditary ataxias: helpful on the group level, particularly in SCA3, but limited in individual patients

Abstract: Background A brief bedside test has recently been introduced by Hoche et al. (Brain, 2018) to screen for the Cerebellar Cognitive Affective Syndrome (CCAS) in patients with cerebellar disease. Objective This multicenter study tested the ability of the CCAS-Scale to diagnose CCAS in individual patients with common forms of hereditary ataxia. Methods A German version of the CCAS-Scale was applied in 30 SCA3, 14 SCA6 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 58 publications
3
6
1
Order By: Relevance
“…This study validated the Chinese version of CCAS-s in patients with acute cerebellar infarction and adjusted the pass/fail diagnostic cut-off scores for CCAS-s tests. The Chinese CCAS-s showed acceptable reliability and validity in cerebellar infarction, whereas with relatively lower speci city and sensitivity than those reported in previous studies 11 . Our analyses further demonstrated that CCAS-s raw scores were correlated with age, education, and ne motor skills.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…This study validated the Chinese version of CCAS-s in patients with acute cerebellar infarction and adjusted the pass/fail diagnostic cut-off scores for CCAS-s tests. The Chinese CCAS-s showed acceptable reliability and validity in cerebellar infarction, whereas with relatively lower speci city and sensitivity than those reported in previous studies 11 . Our analyses further demonstrated that CCAS-s raw scores were correlated with age, education, and ne motor skills.…”
Section: Discussioncontrasting
confidence: 51%
“…Our study also indicated that the cut-off scores of CCAS-s tests may differ among cerebellar diseases. The passing score (sum of cut-off scores for each item of the scale) was 81 for our cerebellar infarction cohort in contrast to 95 for the German hereditary ataxia cohort 7 and 72 for the original validation cohort 4 . The severity of cognitive de cits following cerebellar damages may in part re ect the distinct patterns of disrupted connectivity between the cerebellum and cerebrum in these cerebellar disorders and their diverse clinical presentations 16 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The inferences we can draw in terms of brain-behavior relationships is limited by the heterogeneity of our patient sample. Of note, our sample did include a large number of patients with SCA-3, a genetic variant that typically produces symptoms indicative of cerebellar and extra-cerebellar involvement (56) and is associated with depressed cognitive function (57). Note that 1) this subgroup did not stand out on our measures of strategy discovery or recall, suggesting that the impairment in strategy discovery is related to degeneration of the cerebellum; 2) the number of non-learners was similar in the CD and Control groups, arguing that the observed dissociation between discovery and recall is unlikely to be due to a general cognitive impairment in the CD group; and 3) our results have been corroborated by that of another unpublished dataset using a standard visuomotor rotation task (58).…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence of cerebellar dysfunction, ataxia patients may have a syndrome of impaired executive functions, visuospatial cognition, linguistic functions, and personality changes, named the Cerebellar Cognitive Affective Syndrome (CCAS) [ 22 ]. Consideration of the CCAS in clinical routine is facilitated by the availability of a validated bedside test, the CCAS scale [ 23 ], albeit showing limitations in its application for individual diagnostics [ 24 ].…”
Section: Ataxia-specific Coasmentioning
confidence: 99%